Permeability of coal tar enamel coating to cathodic protection current on pipelines. (20th December 2018) - Yin, Ke; Yang, Yao; Frank Cheng, Y.
Highlights: Measured the permeability of coal tar enamel coating to cathodic protection (CP). The defect-free coal tar enamel coating is impermeable to CP current. For coal tar coatings containing a defect, the CP permeation depends on its size. The threshold diameter of circular coating defects to permit CP current to pass is 1 mm. Abstract: Coal tar enamel (CTE) coatings are the primary coatings used for corrosion protection of oil/gas pipelines which have been usually in service for about fifty years. The compatibility of CTE coatings with cathodic protection (CP) is critical to integrity maintenance of the pipelines. In this work, the permeability of CTE to CP current was investigated in a simulated soil solution through monitoring potential, current and solution pH. Results show that the coatings are CP-impermeable. Even at the practically minimum thickness of 2.30 mm for the coating, the CP permeability is 0.541% only. As the coating thickness increases, the CP permeability reduces rapidly. For the coatings containing defects, the CP permeation depends on their size. In this work, the threshold diameter for circular coating defects present on CTE coating is 1 mm, below which more than 70% of CP current is shielded from permeation.